Literature Review : Kelengkapan Kode Topography dan Morphology pada Kasus Neoplasma - Dian Nur Muslimah; Deasy Rosmala Dewi; Laela Indawati; Lily Widjaja (Yayasan Literasi Sains Indonesia, 2023)
In the Medical Record for determining the cancer diagnosis code (Neoplasm), there are 2 codes, namely the topographic code and the morphology code. These two codes are very important because the topographic code is a code that shows the location of the tumor, while the morphology code is a code that shows the nature of the tumor. If the two codes are not included, it will not determine the level of malignancy of the tumor. The aim of the study was to identify the completeness of the topographic and morphological codes in neoplasm cases. Literature study conducted on 7 journals uploaded online in the span of 2011-2021. Search journals in this study using the keywords